Down-regulation of long non-coding RNA HOTAIR sensitizes breast cancer to trastuzumab - Tianwen Chen (Nature Portfolio, 2019)
Abstract This study aimed to investigate the roles and possible molecular mechanisms of long non-coding RNA HOTAIR in regulating resistance to trastuzumab in breast cancer. Trastuzumab-resistant breast cancer cell line SK-BR-3-TR was assayed for the expression of HOX antisense intergenic RNA (HOTAIR), epithelial-mesenchymal transition (EMT)-related proteins or genes. Methylation levels of TGF- β, PTEN and cyclin-dependent kinase inhibitor 1B (or P27) were determined. In trastuzumab-resistant cell line, the mRNA level of HOTAIR was significantly up-regulated; in addition, the expression of TGF-β, Snail and Vimentin was also up-regulated, E-cadherin was down-regulated while the expression of HER2, PI3K, AKT, mTOR and MAPK in the HER2 receptor pathway and phosphorylation level of HER2 receptor remained unchanged, the methylation levels of the PTEN gene and TGF-β were increased and decreased, respectively. RNA interference downregulated the HOTAIR level and sensitized the cells to trastuzumab. It also resulted in down-regulation of TGF-β, Snail, Vimentin, p-AKT, p-APK and CyclinD1 and up-regulation of E-cadherin, PTEN and P27. Besides, the methylation levels of the PTEN gene and TGF-β were reduced and increased, respectively. Mouse models grafted with SK-BR-3-TR grew faster than with SK-BR-3-TS and siHOTAIR-SK-BR-3-TR.